Psychosocial needs and outcomes of adults with spina bifida: A scoping review, 1974-2023 - Jennifer Emilie Mannino; Heather Reens; Kathryn Smith; Lynn Kysh; Serge' R. Nelson; Yuding Wang; Manu Raam; Michele Roland; Alexander Van Speybroeck; Cecily L. Betz (Health Care Transitions)
Limited evidence exists that serves to guide the field of practice and research pertaining to the long-term issues and needs of adults with spina bifida. Understanding the lived experience of adults with spina bifida has lagged behind considerably resulting in limited evidence-based guidance for individuals with spina bifida and their families and the health care professionals who provide services to this population. Given the paucity of knowledge of the lived experience as it pertains to adulthood, this scoping review was undertaken. More than 10,000 records from 1974 through 2023 were screened based upon the search criteria whose purpose was to examine the research conducted the psychosocial outcomes and needs of adults with spina bifida. A total of 81 articles were included in this review. The findings of this review revealed significant gaps were apparent. There was limited data on adulthood benchmarks of employment, education, community living and social relationships. Limitations associated with the investigations of this review included underpowered samples, lack of longitudinal designs, use of instruments with insufficient psychometrics, and the use of clinical and administrative data sets not designed for research purposes. As the survival rates of individuals with spina bifida continue to improve with medical advances more robust psychosocial research pertaining to this population is needed.